ON THE SECOND ORDER STATISTICS OF THE RATIO OF TWO FISHER-SNEDECOR RANDOM VARIABLES AND ITS APPLICATION TO INTERFERENCE LIMITED COMMUNICATIONS - Stefanović, Časlav; Đošić, Danijel; Panić, Stefan (Bulletin of Natural Sciences Research, 2023)
The paper investigates the higher order statistics of the ratio of two Fisher-Snedecor F (FS-F) random variables (RVs) and its application to wireless communications in the presence of co-channel interference. Namely, the work provides novel expressions for probability density function (PDF), cumulative density function (CDF), level crossing rate (LCR) and average fade duration (AFD) of the ratio of two FS-F RVs. Numerical examples of the analytically derived statistical measures in terms of FS-F multi-path and shadowing parameters are shown and examined. Moreover, the impact of the number of interferes on the considered measures are further presented and examined.
Keywords: 5G; Fisher-Snedecor F (FS-F) distribution; Second order statistics